2016
DOI: 10.1152/ajpcell.00137.2015
|View full text |Cite
|
Sign up to set email alerts
|

KATP channel deficiency in mouse FDB causes an impairment of energy metabolism during fatigue

Abstract: The skeletal muscle ATP-sensitive K (K) channel is crucial in preventing fiber damage and contractile dysfunction, possibly by preventing damaging ATP depletion. The objective of this study was to investigate changes in energy metabolism during fatigue in wild-type and inwardly rectifying K channel (Kir6.2)-deficient (Kir6.2) flexor digitorum brevis (FDB), a muscle that lacks functional K channels. Fatigue was elicited with one tetanic contraction every second. Decreases in ATP and total adenylate levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…An optimum voltage of 20 V was established prior to the experiments to ensure maximal stimulation of the FDB, EDL, and soleus (data not shown). Absolute muscle force data were converted to specific force (N/cm 2 ) using previously described equations for the mathematical estimation of muscle CSA [ 18 ] and physiological cross-sectional area (PCSA) [ 19 ]. The primary difference between CSA and PCSA is the inclusion of the muscle fiber length to muscle length ratio in the PCSA equation.…”
Section: Methodsmentioning
confidence: 99%
“…An optimum voltage of 20 V was established prior to the experiments to ensure maximal stimulation of the FDB, EDL, and soleus (data not shown). Absolute muscle force data were converted to specific force (N/cm 2 ) using previously described equations for the mathematical estimation of muscle CSA [ 18 ] and physiological cross-sectional area (PCSA) [ 19 ]. The primary difference between CSA and PCSA is the inclusion of the muscle fiber length to muscle length ratio in the PCSA equation.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been also shown that K ATP channel-mediated cardioprotection can occur even when action potential shortening is prevented (20) and leads to high-energy phosphate preservation (40) and that K ATP channels play a role in maintaining high-energy phosphates in heart failure (28). With respect to other muscle types, a recent study (49) has shown that metabolism becomes dysfunctional during fatigue in skeletal muscle from Kir6.2 Ϫ/Ϫ mice, although there are likely differences in the role of K ATP channels between cardiac and skeletal muscle, as other groups have shown that Kir6.2 ablation increases lactate and glucose uptake under nonstressed ex vivo condi- Ϫ hearts relative to Kir6.2 ϩ/ϩ hearts (n ϭ 8 hearts/group). C: histological analysis using periodic acid-Schiff stain showed a significantly higher number of glycogen particles in Kir6.2 Ϫ/Ϫ hearts relative to Kir6.2 ϩ/ϩ hearts (n ϭ 3 hearts/group).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding metabolism, K ATP channel openers have previously been shown to preserve myocardial ATP content (40) during ischemic stress, perhaps by interactions with metabolic signaling pathways. Moreover, recent studies have shown altered metabolism in skeletal muscle from Kir6.2 Ϫ/Ϫ tissue (49) and that functional K ATP channels are critical in maintaining high-energy phosphates in the failing heart (28). Proteomic analysis has revealed that cardiac K ATP channels are associated with many proteins, especially those involved in glucose oxidation, fatty acid oxidation, glycolysis (29), and other metabolism pathways (29,59).…”
mentioning
confidence: 99%
“…In fact, daily O2 uptake is greater in Kir6.2 ‐/‐ than in wild‐type mice (Alekseev et al. ; Scott ) and mitochondrial glucose oxidation increases within 60 sec during fatigue in Kir6.2 ‐/‐ FDB bundles and only during recovery in wild‐type bundles (Scott ). So, one compensatory mechanism may be a greater ATP production associated with greater oxidative capacity that reduces the dependency of Kir6.2 ‐/‐ fibers on the myoprotection of KATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility to explain the differences between Kir6.2 -/and glibenclamide-exposed fibers is the fact that Kir6.2 -/represents a chronic loss of KATP channel activity that allows for compensatory mechanisms to develop. In fact, daily O2 uptake is greater in Kir6.2 -/than in wild-type mice (Alekseev et al 2010;Scott 2012) and mitochondrial glucose oxidation increases within 60 sec during fatigue in Kir6.2 -/-FDB bundles and only during recovery in wild-type bundles (Scott 2012). So, one compensatory mechanism may be a greater ATP production associated with greater oxidative capacity that reduces the dependency of Kir6.2 -/fibers on the myoprotection of KATP channels.…”
Section: Differences Between the Two Katp-channeldeficient Modelsmentioning
confidence: 99%